(untitled) (Research, Society and Development, 2022)
Introduction: The pain of childbirth is an experience lived by most women in labor. Non-pharmacological resources can be used to reduce the pain, duration, and risk of maternal and fetal distress in labor. The objective of this study was to evaluate the effects of the use of the birth ball on pain reduction and labor duration. Methods: This is a systematic review, conducted in PubMed, PEDro and SciELO databases in September/2022. Only randomized controlled trials were selected for the search. The research question was: Does the use of the birth ball as a physical therapy resource reduce pain and labor duration? Results: Seventeen studies were found, and six were included. Among the studies analyzed, all evaluated the effect of the use of the birth ball on pain reduction, observing significant difference, while 5 analyzed its effect on labor duration reduction, presenting divergent results. One of the studies allowed the use of the peanut ball, an alternative in cases of epidural anesthesia for maternal positioning. The birth ball is one of the low-cost non-pharmacological resources used in pain management and labor duration, presenting clinical safety, without interfering in maternal and fetal parameters. Conclusion: This review allows us to conclude that the birth ball is a resource that shows positive results in reducing pain during labor, however, there is still no consensus in the literature about its effect on labor duration.